Flow Fields in front of a Cylindrical Obstacle - Yulistiyanto B. (Institute of Research and Community Outreach - Petra Christian University, 2010)
An experimental investigation, conducted in two different flows Reynolds number, was carried out to study the structure of the flow field upstream of a cylindrical obstacle. An Acoustic Doppler Velocity Profiler (ADVP) was used to obtain instantaneously the three directions of the mean velocity. Results of the experiments show the longitudinal velocities, , decrease approaching the cylinder, their distribution becomes more uniform and close to the bed a reverse flow is noticeable with increasing importance. The downward velocity component is clearly shown, continuing with the return flow near the bed, forming a vortex. At positions where the vortex appears upstream from the cylinder, a large increase of the three components of the turbulence intensities is remarked. Approaching the cylinder, one observes the shear stress decreases, having the opposite direction at positions close to the cylinder. A zero value of shear stress should be at the separation point.